2011
DOI: 10.5632/jila.74.633
|View full text |Cite
|
Sign up to set email alerts
|

Relation of quantitative index and subjective evaluation for sequence landscape in Oze national park

Abstract: There are many kinds of landscape materials in Oze national park. Visitors of the Oze can be seen such materials as sequence landscapes due to walking on boardwalks. Some subjective evaluations of the landscape at individual positions were performed by image survey. Therefore, in order to extract interesting position with characteristic landscape, sequence landscape in Oze should be also evaluated. Moreover, the landscapes during the walking are analyzed continuously. On the other hand, landscape analysis is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Moreover, Kunii and Furuya's (2010) analyzed sequential landscapes using quantitative methods in National Parks 19) . In addition, Kunii and Furuya's continuing study also surveyed public evaluations and revealed the relationship between quantitative data and subjective evaluations 20) (Kunii and Furuya, 2011). All in all, natural landscape research was found to have a high affinity for quantitative evaluations.…”
Section: Natural Landscape Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Kunii and Furuya's (2010) analyzed sequential landscapes using quantitative methods in National Parks 19) . In addition, Kunii and Furuya's continuing study also surveyed public evaluations and revealed the relationship between quantitative data and subjective evaluations 20) (Kunii and Furuya, 2011). All in all, natural landscape research was found to have a high affinity for quantitative evaluations.…”
Section: Natural Landscape Researchmentioning
confidence: 99%
“…Continuing studies 19,20) quantitative evaluation (5) attributes (4) likable scenery (3) recognition (2) [road landscape design system 27) , design theory of bridge, landscape regeneration in port 24) ] conservation and utilization (3) recognition and assessment (10) [CAVE, fractal dimension, remove utility poles 26) , overhead bridge, image evaluation ]…”
Section: Natural Landscapementioning
confidence: 99%
See 1 more Smart Citation